The Impact of Environmental, Social and Governance Reporting on Corporate Performance of Energy and Minerals Sector in South Africa - Chandabemba Ngwenya, Duncan; Mabeta, Joshua; Asiedu, Emmanuel; Jilek, Milan; Cudlínová, Eva (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Environmental, Social, and Governance (ESG) issues impact corporate strategy and performance; hence, reporting on environmental and social strategies within an effective corporate governance system enhances corporate performance and sustainability. This study contributes to the existing literature on ESG reporting by providing empirical evidence on the influence of ESG reporting on corporate performance, specifically exploring its impact using the gross profits of firms in the energy and minerals sector in South Africa. The research analyses a dataset of five firms spanning the period from 2013 to 202. Using correlation analysis, the results indicate that the relationship between gross profit and ESG metrics varies. In some years, a positive correlation emerges, indicating that companies with stronger ESG performance tend to see financial improvements. Companies with consistently high gross profit in earlier years tend to sustain their profitability over time, reflecting financial stability and resilience. However, in other instances, the correlation is weak or even negative, suggesting that investments in ESG initiatives may initially reduce profit margins before yielding long-term financial benefits. These findings indicate a growing alignment between ESG reporting and financial performance, suggesting that sustainability-driven business models are increasingly financially viable and reinforcing the need to integrate sustainability into business strategies.